Tourism on ice: environmental impact assessment of Antarctic tourism - Rootes, D; Kriwoken, L (2000)
The evolving institutional arrangements for the environmental impact assessment (EIA) of Antarctic tourism are evaluated and suggestions made on its future. The EIA provisions of the 1991 Madrid Protocol are legally required by companies, registered in Treaty signatory states, in planning and managing all tourist activities. An assessment of the three tiers of EIA established under the Protocol is presented. Potential solutions for assessing impacts of Antarctic tourism include adoption of strategic environmental assessment, regional assessments and environmental auditing. International best practice methods should be adopted in the initial environmental evaluation along with greater consistency of EIA application through indicative lists and guidelines, a dedicated database of Antarctic EIAs and increased cooperation in the EIA process between the tourism industry and Antarctic Treaty Consultative Parties that support Antarctic logistics and science.